Sebuah Kerangka Kerja untuk mengembangkan e-Tracer study berbasis Sistem Cerdas - Rizaldi Akbar; Rahmi Hajriyanti (KITA Institute, 2020)
Tracer studies are a method used by tertiary institutions to track, monitor, and supervise graduates that have been produced by tertiary institutions. These activities can make a performance measurement related to the implementation of education so far. Currently, the tracer study has been developed to become a system that can provide decisions and measure graduates using an intelligent agent (AI). In this study, the authors used a descriptive research method, namely developing an information system based on existing data and developed using PHP software, and the Dynamic System Development Method (DSDM) is a system development method. Researchers have implemented an AI integration framework in a web-based tracer study architecture. System evaluation is used as the next research iteration of the proposed decision support system, this study also aims to monitor graduates. With the existence of an intelligent system-based e-tracer study, it has become an evolution in studying artificial intelligence to support monitoring and as a tool in increasing graduates in Higher Education.